Non-invasive therapeutics for neurotrauma: a mechanistic overview - James D. O'Leary; Bevan S. Main; Mark P. Burns (Frontiers in Neurology)
Traumatic brain injury is a leading cause of death and a major risk factor for the development of both memory and motor disorders. To date, there are no proven interventions to improve patient outcome after neurotrauma. A promising avenue of treatment has emerged in the use of non-invasive therapies for recovery after brain injury. A number of non-invasive brain stimulation techniques have been developed, such as transcranial direct current stimulation, transcranial magnetic stimulation and vagus nerve stimulation, as well as low intensity ultrasound stimulation and photobiomodulation therapy. However, standardized treatment regimens have not been developed. There is a clear need to better understand the underlying mechanisms of non-invasive therapeutics on brain injury pathology so as to more effectively guide treatment strategy. Here we review the current literature of non-invasive therapies in preclinical neurotrauma and offer insight into the potential mechanism of action and novel targets for the treatment of traumatic brain injury.